Implementasi Pengujian Black Box menggunakan Teknik Equivalents Partitions pada Aplikasi Pendaftaran Commuter Line Berbasis Web - Muhamad Diky Oktafian; Muhamad Azi Haetami; Muhamad Jibril; Reyhan Said; Teti Desyani (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
Computer Program that contains defectives (mistakes) can cause a disadvantage that can affect to stakeholders. The disadvantaged can take the shape of money related, time, and others. So sometime recently the program is executed it has to be testing. Testing on an application proposed to check the program is running legitimately or not. In testing, this computer program will utilize Black Box Testing. Black Box Testing Strategy had a few strategies, Equivalence Partitions, Boundary Value Analysis, Sample Testing, etc. From many testing methods, we will use the Equivalence Partitions. Equivalence Partitions method is a test based on data input for each form where the application system of performance data information each menu input would be tested and grouped accord to the function whether valid or invalid. Testing is doing on the Application form that will be in the content from the data that suitable with personal data. The final results show there is still much lack when valid data will be inputted causes data stored in the database to be incompatible with the expected data. The results of this test would be used to improve the application at performance data for the future. In the end, the application could handle normal and abnormal data with a percentage of success 91,67%.